Genetic Manipulation of Human Intestinal Enteroids Demonstrates the Necessity of a Functional Fucosyltransferase 2 Gene for Secretor-Dependent Human Norovirus Infection - Kei Haga (mBio, 2020)
Several studies have demonstrated that secretor status is associated with susceptibility to human norovirus (HuNoV) infection; however, previous reports found that FUT2 expression is not sufficient to allow infection with HuNoV in a variety of continuous laboratory cell lines. Which cellular factor(s) regulates susceptibility to HuNoV infection remains unknown. We used genetic manipulation of HIE cultures to show that secretor status determined by FUT2 gene expression is necessary and sufficient to support HuNoV replication based on analyses of isogenic lines that lack or express FUT2. Fucosylation of HBGAs is critical for initial binding and for modification of another putative receptor(s) in HIEs needed for virus uptake or uncoating and necessary for successful infection by GI.1 and several GII HuNoV strains.Human noroviruses (HuNoVs) are the leading cause of nonbacterial gastroenteritis worldwide. Histo-blood group antigen (HBGA) expression is an important susceptibility factor for HuNoV infection based on controlled human infection models and epidemiologic studies that show an association of secretor status with infection caused by several genotypes. The fucosyltransferase 2 gene (FUT2) affects HBGA expression in intestinal epithelial cells; secretors express a functional FUT2 enzyme, while nonsecretors lack this enzyme and are highly resistant to infection and gastroenteritis caused by many HuNoV strains. These epidemiologic associations are confirmed by infections in stem cell-derived human intestinal enteroid (HIE) cultures. GII.4 HuNoV does not replicate in HIE cultures derived from nonsecretor individuals, while HIEs from secretors are permissive to infection. However, whether FUT2 expression alone is critical for infection remains unproven, since routinely used secretor-positive transformed cell lines are resistant to HuNoV replication. To evaluate the role of FUT2 in HuNoV replication, we used CRISPR or overexpression to genetically manipulate FUT2 gene function to produce isogenic HIE lines with or without FUT2 expression. We show that FUT2 expression alone affects both HuNoV binding to the HIE cell surface and susceptibility to HuNoV infection. These findings indicate that initial binding to a molecule(s) glycosylated by FUT2 is critical for HuNoV infection and that the HuNoV receptor is present in nonsecretor HIEs. In addition to HuNoV studies, these isogenic HIE lines will be useful tools to study other enteric microbes where infection and/or disease outcome is associated with secretor status.